Does being physically active prevent future disability in older people?: attenuated effects when taking time-dependent confounders into account - Kreisel, Stefan H.; Blahak, Christian; Bäzner, Hansjörg; Hennerici, Michael G. (BMC geriatrics, 2017)
Causal experimental evidence that physical activity prevents disability in older people is sparse. Being physically active has nonetheless been shown to be associated with disability-free survival in observational studies. Observational studies are, however, prone to bias introduced by time-dependent confounding. Time-dependent confounding occurs when an exposure (e.g. being physically active at some time-point) potentially affects the future status of a confounder (such as depression sometime later), and both variables have an effect on latter outcome (i.e. disability). “Conventional” analysis with e.g. Cox-regression is the mainstay when analyzing longitudinal observational studies. Unfortunately, it does not provide unbiased estimates in the presence of time-dependent confounding. Marginal structural models (MSM) - a relatively new class of causal models - have the potential to adequately account for time-dependent confounding.